2003
DOI: 10.1038/sj.onc.1206883
|View full text |Cite
|
Sign up to set email alerts
|

Role of genetic background in induced instability

Abstract: Genomic instability is effectively induced by ionizing radiation. Recently, evidence has accumulated supporting a relationship between genetic background and the radiation-induced genomic instability phenotype. This is possibly due to alterations in proteins responsible for maintenance of genomic integrity or altered oxidative metabolism. Studies in human cell lines, human primary cells, and mouse models have been performed predominantly using high linear energy transfer (LET) radiation, or high doses of low L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 62 publications
(49 reference statements)
2
14
1
Order By: Relevance
“…There is a long, intensive and partially controversial discussion on these 'non-targeted effects' or 'bystander effects', especially in the context of low-dose radiation , Hooker et al 2004, Belyakov et al 2005, Brooks 2005, Mothersill & Seymour 2005, Barcellos-Hoff & Costes 2006, Chaudhry 2006. The term 'nontargeted' thereby indicates that cells that have not seen radiation are affected by neighbouring irradiated cells through intercellular signaling mechanisms (Kadhim et al 1992, Nagasawa & Little 1992, Huang et al 1995, 2003, Deshpande et al 1996, Prise et al 1998, Little 2000, Lorimore et al 2003, Mothersill & Seymour 2003, 2006a, 2006b, 2006c, Azzam et al 2003, 2004, Barcellos-Hoff & Costes 2006, Chaudhry 2006, Spitz et al 2004, Shao et al 2005, Wright & Coates 2006. The interplay between induction of genomic stability and adaptive radiation-induced bystander effects may occur at extremely low doses of radiation (Hooker et al 2004, Zeng et al 2006.…”
Section: Low Dose Radiation and Non-targeted Effectsmentioning
confidence: 96%
See 1 more Smart Citation
“…There is a long, intensive and partially controversial discussion on these 'non-targeted effects' or 'bystander effects', especially in the context of low-dose radiation , Hooker et al 2004, Belyakov et al 2005, Brooks 2005, Mothersill & Seymour 2005, Barcellos-Hoff & Costes 2006, Chaudhry 2006. The term 'nontargeted' thereby indicates that cells that have not seen radiation are affected by neighbouring irradiated cells through intercellular signaling mechanisms (Kadhim et al 1992, Nagasawa & Little 1992, Huang et al 1995, 2003, Deshpande et al 1996, Prise et al 1998, Little 2000, Lorimore et al 2003, Mothersill & Seymour 2003, 2006a, 2006b, 2006c, Azzam et al 2003, 2004, Barcellos-Hoff & Costes 2006, Chaudhry 2006, Spitz et al 2004, Shao et al 2005, Wright & Coates 2006. The interplay between induction of genomic stability and adaptive radiation-induced bystander effects may occur at extremely low doses of radiation (Hooker et al 2004, Zeng et al 2006.…”
Section: Low Dose Radiation and Non-targeted Effectsmentioning
confidence: 96%
“…Non-targeted effects (bystander effects) have been reported for micronucleus formation , Shao et al 2005, mutagenic effects (Zhou et al 2000), sister chromatide exchange (Nagasawa & Little 1992, Deshpande et al 1996, genomic instability (Kadhim et al 1992, Morgan et al 1996, Limoli et al 1999, Limoli & Giedzinski 2003, Mothersill & Seymour 2003, Hooker et al 2004, Huang et al 2007, reduction in clonogenic survival (Mothersill & Seymour 1997), apoptosis (Kadhim et al 1995, Kadhim 2003, Lyng et al 2006, increase in tumorigenic potential (Barcellos-Hoff & Ravani 2000, Barcellos-Hoff 2001, decrease in observable transformation frequency (Azzam et al 1994, Pant et al 2003, Redpath 2005, Ko et al 2006, resistance against renewed irradiation with a challenging dose (Hooker et al 2004, Prise 2006, Zeng et al 2006) and removal of transformed cells via intercellular induction of apoptosis (Portess et al 2007). The decrease in detectable transformation frequency and removal of transformed cells through low dose radiation effects has been included into models for the mathematical simulation of multistage oncogenesis (Schö llnberger et al 2002, Scott et al 2003, Scott 2004, Schö llnberger & Eckl 2007.…”
Section: Low Dose Radiation and Non-targeted Effectsmentioning
confidence: 98%
“…Kadhim [5] has reviewed the impact of potential genetic contributions to induced genomic instability in humans in detail and concluded that this inherent variability is likely due to alterations in proteins responsible for the maintenance of genomic integrity or altered oxidative metabolism. When the bone marrow cells of haematologically normal individuals were exposed to alpha-particles in vitro and examined for non-clonal cytogenetic aberrations in clonal descendants of the haemopoietic stem cells, Kadhim et al [6] observed cytogenetic evidence of radiation-induced genomic instability in two of four individuals studied.…”
Section: Induced Chromosomal Instability In Radiation-exposed Human Pmentioning
confidence: 99%
“…Low dose radiation has been shown to induce a decrease in observable transformation frequency [33-36.41-43]. Removal of transformed cells through apoptosis has been discussed as a conceivable mechanism for nontargeted antioncogenic low dose radiation effects [30,45,46]. The report by Portess et al [30] gives a mechanistic explanation for selective elimination of transformed cells by low dose radiation.…”
Section: Introductionmentioning
confidence: 98%